Influence of water stress on leaf litter decomposition in upland Amazonian forest - Castro, Rosecélia Moreira Silva; Ruivo, Maria de Lourdes Pinheiro; Santos, Seidel Ferreira dos; Rodrigues, Possidônio Guimarães (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2017)
In this study, the influence of water stress on leaf litter decomposition was verified. Collections were carried out in the Caxiuanã National Forest (Pará), in an experimental area where Amazon forest was covered with plastic sheets that prevented rainwater from reaching the ground and in an adjacent control area under natural conditions. In each area 180 leaf-filled bags of three different mesh sizes (0.2 mm, 2.0 mm, and 1.0 mm) were fixed to the ground and collected after intervals of 60, 120, 210 and 300 days. Decomposition rates were found to be lower in the rain-deprived forest. Variation in mesh size was significant for the amount of remaining material. For the 60 and 120 day decomposition periods the loss of leaf litter mass was approximately 50% of the remaining material, and for the 300 day period the remaining material suffered a reduction of 68.9%, 70.1%, and 54.4% for thick, medium, and fine mesh bags, respectively. No statistically significant differences were found between the two experimental areas after 12 months.